Пусть второй отрезок = x +8,
Пусть третий отрезок= x +11
Пусть первый отрезок= x
x + x+8 + x+11 = 174
3x=174-8-11
x=51,(6)
Второй отрезок= 51,6 + 8= 59,6
третий отрезок= 51,6+ 11= 62, 6
Объяснение:
вроде так, но я не уверена
Х+(х+8)+(х+11)=174
3х+19=174
3х=174-19
3х=155
Х=155:3
Пусть второй отрезок = x +8,
Пусть третий отрезок= x +11
Пусть первый отрезок= x
x + x+8 + x+11 = 174
3x=174-8-11
x=51,(6)
Второй отрезок= 51,6 + 8= 59,6
третий отрезок= 51,6+ 11= 62, 6
Объяснение:
вроде так, но я не уверена
Объяснение:
Х+(х+8)+(х+11)=174
3х+19=174
3х=174-19
3х=155
Х=155:3